2019
DOI: 10.1071/rd18338
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics–genomics data integration and expression quantitative trait loci analyses in oocyte donors and embryo recipients for improving invitro production of dairy cattle embryos

Abstract: In this paper we first provide a brief review of main results from our previously published studies on genome-wide gene expression (transcriptomics) in donor and recipient cattle used in invitro production (IVP) of embryos and embryo transfer (ET). Then, we present novel results from applying integrative systems genomics and biological analyses where transcriptomics data are combined with genomic data in both donor and recipient cattle to map expression quantitative trait loci (eQTLs). The eQTLs are genetic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The identification of biomarkers associated to increased performance in oocyte donors would be a major step for IVP efficiency improvement and has been the focus of many studies (Kadarmideen & Mazzoni, 2019; Kussano et al, 2016; Labrecque & Sirard, 2014; Mazzoni et al, 2017). Oocyte developmental capacity is affected by several factors, such as chromosomal aneuploidies (Mikwar et al, 2020; Patrizio et al, 2007), mitochondrial dysfunction (Cimadomo et al, 2018), extracellular vesicles lipid profile (da Silveira et al, 2021), and follicular fluid contents such as glucose, pyruvate, cholesterol, and oestradiol (Alves et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of biomarkers associated to increased performance in oocyte donors would be a major step for IVP efficiency improvement and has been the focus of many studies (Kadarmideen & Mazzoni, 2019; Kussano et al, 2016; Labrecque & Sirard, 2014; Mazzoni et al, 2017). Oocyte developmental capacity is affected by several factors, such as chromosomal aneuploidies (Mikwar et al, 2020; Patrizio et al, 2007), mitochondrial dysfunction (Cimadomo et al, 2018), extracellular vesicles lipid profile (da Silveira et al, 2021), and follicular fluid contents such as glucose, pyruvate, cholesterol, and oestradiol (Alves et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Differences between oocytes showing distinct performance have been described regarding RNA content and early atresia (Mazzoni et al, 2017). An interesting study associated genomic eQTLs to IVP performance (Kadarmideen & Mazzoni, 2019), but to date, no application is available in genomic selection approaches, and broader studies confirming candidate genes and superior donor performance are required.…”
Section: Discussionmentioning
confidence: 99%
“…This study evidenced that FRSOD downregulated expression of cyclin B1 ( Ccnb1 ) and zygote arrest 1 ( Zar1 ) genes. The Ccnb1 gene has been identified as in vitro embryo production (IVP) parameter of donor cow quality [ 35 ], and increased expression of Ccnb1 is associated with improved oocyte maturation in vitro and post-maturation development [ 36 , 37 ]. In contrast, a decrease in Ccnb1 expression has been observed in aged porcine oocytes [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression QTL studies have been reported for several complex traits; however, only a few of them have focused on fertility in cattle. Kadarmideen and Mazzoni [19] reported eQTLs affecting genes in the bovine follicular cells and the endometrium of dairy cows. The eQTL-modulated genes were associated with the quality of in vitro-produced embryos and endometrial receptivity [19].…”
Section: Introductionmentioning
confidence: 99%